Effect of end‐tidal CO2 clamping on cerebrovascular function, oxygenation, and performance during 15‐km time trial cycling in severe normobaric hypoxia: the role of cerebral O2 delivery. Issue 3 (28th August 2013) - Fan, Jui‐Lin; Bourdillon, Nicolas; Kayser, Bengt
Abstract During heavy exercise, hyperventilation‐induced hypocapnia leads to cerebral vasoconstriction, resulting in a reduction in cerebral blood flow (CBF). A reduction in CBF would impair cerebral O2 delivery and potentially account for reduced exercise performance in hypoxia. We tested the hypothesis that end‐tidal Pco2 (PETCO2) clamping in hypoxic exercise would prevent the hypocapnia‐induced reduction in CBF during heavy exercise, thus improving exercise performance. We measured PETCO2, middle cerebral artery velocity (MCAv; index of CBF), prefrontal cerebral cortex oxygenation (cerebral O2Hb; index of cerebral oxygenation), cerebral O2 delivery (DO2), and leg muscle oxygenation (muscle O2Hb) in 10 healthy men (age 27 ± 7 years; VO2max 63.3 ± 6.6 mL/kg/min; mean ± SD) during simulated 15‐km time trial cycling (TT) in normoxia and hypoxia (FIO2 = 0.10) with and without CO2 clamping. During exercise, hypoxia elevated MCAv and lowered cerebral O2Hb, cerebral DO2, and muscle O2Hb (P < 0.001). CO2 clamping elevated PETCO2 and MCAv during exercise in both normoxic and hypoxic conditions (P < 0.001 and P = 0.024), but had no effect on either cerebral and muscle O2Hb (P = 0.118 and P = 0.124). Nevertheless, CO2 clamping elevated cerebral DO2 during TT in both normoxic and hypoxic conditions (P < 0.001). CO2 clamping restored cerebral DO2 to normoxic values during TT in hypoxia and tended to have a greater effect on TT performance in hypoxia compared to normoxia (P = 0.097). However, post hoc analysis revealed no effect of CO2 clamping on TT performance either in normoxia (P = 0.588) or in hypoxia (P = 0.108). Our findings confirm that the hyperventilation‐induced hypocapnia and the subsequent drop in cerebral oxygenation are unlikely to be the cause of the reduced endurance exercise performance in hypoxia.